P01.139 Safety and adverse event profile of tumor treating fields use in the EMEA region - a real-world data analysis. (19th September 2018) - Glas, M; Kebir, S
Abstract: Background: Tumor Treating Fields (TTFields) is approved for the treatment of newly diagnosed and recurrent glioblastoma. The efficacy and safety of TTFields in newly diagnosed GBM was previously demonstrated in the EF-14 phase 3 trial (n=695). Optune + temozolomide significantly improved survival outcomes compared to temozolomide alone (median OS: 20.9 vs 16.0 months, p<0.001). Post-market surveillance data were collected for patients who used Optune. Here, we report the adverse event profile of Optune use in the EMEA region in real-world setting. Material and Methods: A review of global post-market surveillance data including patients treated with Optune in the EMEA region. Adverse events reported to the Novocure safety department were analyzed based on the MedDRA body system (system organ class) preferred terms. Results: A total of 8025 patients were treated with Optune globally (newly diagnosed glioblastoma 46.1%, recurrent glioblastoma 46.2%, other 7.7%). Of these 1496 patients were treated in the EMEA region (Israel, Switzerland, Germany and other European countries). In this cohort, as expected, skin reaction was the most prevalent adverse event affecting 25% of patients. Other adverse events included: General decline in health (24%), Nervous system disorders (18%), Injury at any location (5%), Gastrointestinal disorders (4%), and Musculoskeletal disorders (3%). Conclusion: This retrospective analysis demonstrates the safety profile of Optune in an EMEA patient cohort. The most common adverse event registered was skin reaction, which was also found in the phase 3 EF-11 trial for recurrent GBM and in the EF-14 trial for newly diagnosed GBM patients. No other device-related adverse events were reported. In summary, these results emphasize the safety of Optune in GBM treatment and its consequent adoption in the EMEA region.